EFFECTS OF MERGERS AND ACQUISITIONS ON SHAREHOLDERS’ WEALTH IN NIGERIAN BANKING INDUSTRY - Onikoyi; Adegboyega, Idris; Awolusi; Dele, Olawumi (British Journal of Marketing Studies, 2014)
Mergers and acquisitions that took place in Nigerian Banking Industry in 2005 were to create wealth for shareholders, provide solid and reliable banking institutions that can compete favourably with foreign financial institutions. Going by market value of the merged banks, shareholders wealth had been eroded, in some cases completely destroyed. The visible problems that confront the shareholders of merged banks include melt down of market prices of their shares on the stock market, depletion of shareholders fund due to huge losses incurred by the merged banks and lack of dividend pay out to the shareholders. Exploratory and correlation research designs were used. The population of this study is twenty five (25) consolidated banks as at 1st January, 2006. Stratified Sampling technique was adopted to arrive at fifteen (15) merged banks. Questionnaires were distributed to the staff of the merged banks. The instrument was validated and Cronbach’s Alpha coefficient result of 0.708 was obtained indicating the internal consistency of the instrument. Five hundred and fifty-seven (557) questionnaires were administered and a response rate of 58.3% was obtained. The findings of study showed that there was a significant relationship between shareholders wealth and capital base (?- value of 0.000), market share (?- value of 0.000), bank revenue (?- value of 0.000), cost savings (?- value of 0.000). The study concluded that mergers and acquisitions have positive effect on the shareholders wealth. The implication of findings is that, new capital brought in by shareholders of merged banks increase the size of banks total assets and revolutionized the way banks do their business. The study recommends that banks’ management should give proper attention to scope and scale of economies; eliminate redundancy, corrupt and inefficient staff; it is imperative for shareholders to always bring in fresh capital and Government should give bail-out loans to banks in distress.